(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3jHOC HHGH fhGRd GdhcGdGJ s
(3BNQgG (B:s
(3hQMe Gddg ef bQC gPG GdcJGH hWGdYg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG CHOkG Edi jhe GdOjf s
(3HChdg agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B517s
Keywords: (3Gdabg GdeGdcjs